Firms as Clubs in Walrasian Markets with Private Information - Prescott, Edward Simpson; Townsend, Robert M. (Journal of Political Economy, 2006)
We incorporate multiagent, principal‐agent theory into general equilibrium analysis. The traded commodities are multiagent contracts that include a description of the individual’s job, effort level, and state‐contingent consumption. These contracts are club goods. The competitive equilibrium and the Pareto program are formulated. The contracts are identified with firms, so the market determines which firms exist and who is assigned to which firm in what capacity. An example is provided in which the internal organization of firms and the distribution of firm classes vary with the aggregate capital endowment and its distribution across agents. A simplex‐based algorithm for solving the Pareto program is developed.